Coculture of adipose‐derived mesenchymal stem cells/macrophages on decellularized placental sponge promotes differentiation into the osteogenic lineage. Issue 1 (7th September 2022) - Khosrowpour, Zahra; Hashemi, Seyed Mahmoud; Mohammadi‐Yeganeh, Samira; Moghtadaei, Mehdi; Brouki Milan, Peiman; Moroni, Lorenzo; Kundu, Subhas C.; Gholipourmalekabadi, Mazaher
Abstract: Background: Several factors like three‐dimensional microstructure, growth factors, cytokines, cell–cell communication, and coculture with functional cells can affect the stem cells behavior and differentiation. The purpose of this study was to investigate the potential of decellularized placental sponge as adipose‐derived mesenchymal stem cells (AD‐MSCs) and macrophage coculture systems, and guiding the osteogenic differentiation of stem cells. Methods: The decellularized placental sponge (DPS) was fabricated, and its mechanical characteristics were evaluated using degradation assay, swelling rate, and pore size determination. Its structure was also investigated using hematoxylin and eosin staining and scanning electron microscopy. Mouse peritoneal macrophages and AD‐MSCs were isolated and characterized. The differentiation potential of AD‐MSCs co‐cultured with macrophages was evaluated by RT‐qPCR of osteogenic genes on the surface of DPS. The in vivo biocompatibility of DPS was determined by subcutaneous implantation of scaffold and histological evaluations of the implanted site. Results: The DPS had 67% porosity with an average pore size of 238 μm. The in vitro degradation assay showed around 25% weight loss during 30 days in PBS. The swelling rate was around 50% during 72 h. The coculture of AD‐MSCs/macrophages on the DPS showed a significant upregulation of four differentiation osteogenic lineage genes in AD‐MSCs on days 14 and 21 and a significantly higher mineralization rate than the groups without DPS. Subcutaneous implantation of DPS showed in vivo biocompatibility of scaffold during 28 days follow‐up. Conclusions: Our findings suggest the decellularized placental sponge as an excellent bone substitute providing a naturally derived matrix substrate with biostructure close to the natural bone that guided differentiation of stem cells toward bone cells and a promising coculture substrate for crosstalk of macrophage and mesenchymal stem cells in vitro. Abstract : This study presents the coculture of adipose‐derived mesenchymal stem cells/macrophages on the decellularized placental sponge with a significant upregulation of differentiation osteogenic lineage genes in AD‐MSCs on days 14 and 21. Our findings suggest the DPS as an excellent bone substitute providing a naturally derived matrix substrate with biostructure close to natural bone, a promising coculture substrate for crosstalk of macrophage and AD‐MSCs in vitro, and guiding the differentiation of stem cells toward bone cells.